Transfer of Peptostreptococcus parvulus (Weinberg, Nativelle, and Prévot 1937) Smith 1957 to the Genus Streptococcus: Streptococcus parvulus (Weinberg, Nativelle, and Prévot 1937) comb. nov., nom. rev., emend. - CATO, ELIZABETH P. (International Journal of Systematic and Evolutionary Microbiology, 1983)
On the basis of increased fermentative ability when growth is stimulated by Tween 80, with the production of large amounts of lactic acid and only traces of acetic, succinic, or formic acid, it is proposed that Peptostreptococcus parvulus (Weinberg, Nativelle, and Prévot 1937) Smith 1957 be returned to the genus Streptococcus, where it was placed by the original authors. The description has been amended to reflect the increased biochemical activity of strains of this species when all media contain 0.02% Tween 80. The type strain of Streptococcus parvulus (Weinberg, Nativelle, and Prévot 1937) comb. nov., nom. rev. (VPI 0546) has been deposited in the American Type Culture Collection as ATCC 33793.